Inhibitory potential of three zinc chelating agents against the proteolytic, hemorrhagic, and myotoxic activities of Echis carinatus venom. (January 2015) - Nanjaraj Urs, Ankanahalli N; Yariswamy, Manjunath; Ramakrishnan, Chandrasekaran; Joshi, Vikram; Suvilesh, Kanve Nagaraj; Savitha, Mysore Natarajan; Velmurugan, Devadasan; Vishwanath, Bannikuppe Sannanayak
Abstract: Viperbites undeniably cause local manifestations such as hemorrhage and myotoxicity involving substantial degradation of extracellular matrix (ECM) at the site of envenomation and lead to progressive tissue damage and necrosis. The principle toxin responsible is attributed to snake venom metalloproteases (SVMPs). Treatment of such progressive tissue damage induced by SVMPs has become a challenging task for researchers and medical practitioners who are in quest of SVMPs inhibitors. In this study, we have evaluated the inhibitory potential of three specific zinc (Zn 2+ ) chelating agents; N, N, N′, N′-tetrakis (2-pyridylmethyl) ethane-1, 2-diamine (TPEN), diethylene triamine pentaacetic acid (DTPA), tetraethyl thiuram disulfide (TTD) on Echis carinatus venom (ECV) induced hemorrhage and myotoxicity. Amongst them, TPEN has high affinity for Zn 2+ and revealed potent inhibition of ECV metalloproteases (ECVMPs) in vitro (IC50 : 6.7 μM) compared to DTPA and TTD. The specificity of TPEN towards Zn 2+ was confirmed by spectral and docking studies. Further, TPEN, DTPA, and TTD completely blocked the hemorrhagic and myotoxic activities of ECV in a dose dependent manner upon co-injection; whereas, only TPEN successfully neutralized hemorrhage and myotoxicity following independent injection. Histological examinations revealed that TPEN effectively prevents degradation of dermis and basement membrane surrounding the blood vessels in mouse skin sections. TPEN also prevents muscle necrosis and accumulation of inflammatory cells at the site of ECV injections. In conclusion, a high degree of structural and functional homology between mammalian MMPs and SVMPs suggests that specific Zn 2+ chelators currently in clinical practice could be potent first aid therapeutic agents in snakebite management, particularly for local tissue damage. Graphical abstract: Highlights: Local toxicity induced by Echis carinatus venom is attributed to metalloproteases. Local toxicity due to SVMPs include progressive hemorrhage and myotoxicity. Specific Zn 2+ chelators neutralized both enzymatic and pharmacological activities. Specific Zn 2+ chelators can be exploited to complement anti-snake venom therapy.